Assessing information literacy of the selected high school students of Saint Louis High School - Philex with emphasis on library instruction - Ganipes, Broderick T.; Dela Torre, Nathalie N.; Saint Louis High School - Philex (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
The advancement of information brought about by the development in technology required simple and complex skills that needed to be learned in order to adapt and to be at pace with the past changes. Information literacy became a must, not just a luxury for everyone, the students, professionals, and the society of a whole. Information literacy assessment is the first step to fine tune traditional practices and include the newer development and technologies in the current practice in achieving information literacy.
The study focused on selected high school students from Saint Louis High School - Philex who were surveyed regarding Library Instruction and its components. This study used a revised questionnaire based on previous studies and the Information Literacy Competency Standards for Higher Education published by the Association of College and Research Libraries and the American Library Association. This study focused on assessment of the information literacy level of the respondents, and determining the relationships of independent variables such as gender, financial status, parents' educational achievement, age, academic performance, frequency of library visits and use, and library instruction towards information literacy.
This study found out that more than half of the students of Saint Louis High School - Philex were rated below average in information literacy based on their library instruction literacy results. The students' rating on basic library search skills was average while their resource evaluation skills and source evaluation skills was rated below average. Only 12.1 of the respondents scored an average or better rating in each of the three components of library skills literacy. Therefore, only 12.1 of the 280 respondents are information literate. The students need follow up instruction especially in searching among periodical articles, scientific journals, periodical indexes and abstracts, narrowing electronic searches, library catalog, and search engines. Additional instruction should focus on familiarization with the proper uses of encyclopedias, dictionaries, almanacs, and the internet. The students should be trained extensively on the use of government sources, credible web pages and domains, evaluating the date of sources, citing reference materials, narrowing searches, and properly using descriptors.
This study found out that age or year level and academic performance are the only factors that had significant although weak relationship with the total information literacy result. Other factors such as gender, family annual income,parents' academic achievement, and frequency of library use may have an impact on information literacy competence but their statistic association are not significant.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information literacy -- Philippines -- Baguio City -- Evaluation; Library orientation for high school students -- Philippines -- Baguio City